2006
DOI: 10.1097/01.mpg.0000226374.18494.14
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pro‐Inflammatory Cytokines in Inflammatory Bowel Disease Growth Retardation

Abstract: Childhood inflammatory bowel disease (IBD) especially those with Crohn disease is commonly complicated by faltering growth and pubertal delay. Pro-inflammatory cytokines are often elevated in IBD and may affect linear growth and puberty either systemically or at the level of the growth plate. Further study of the underlying mechanisms of the deleterious effects of cytokines on the growth plate may improve management of faltering growth in childhood IBD. Well-controlled clinical studies of the respective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 107 publications
1
64
0
3
Order By: Relevance
“…Chronic inflammatory diseases such as juvenile idiopathic arthritis and inflammatory bowel disease often lead to childhood growth retardation through a number of proposed mechanisms that includes nutritional deficiency, chronic inflammation, increased catabolism, defects in the growth hormone (GH)/insulin-like growth factor-I (IGF-I) axis and use of glucocorticoids (MacRae et al 2006a, Wong et al 2006. Levels of proinflammatory cytokines, such as tumour necrosis factor (TNF)-a and interleukin (IL)-1b are often raised in these diseases, and measures that block TNF-a action, such as anti-TNF therapy, lead to an improvement in growth.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammatory diseases such as juvenile idiopathic arthritis and inflammatory bowel disease often lead to childhood growth retardation through a number of proposed mechanisms that includes nutritional deficiency, chronic inflammation, increased catabolism, defects in the growth hormone (GH)/insulin-like growth factor-I (IGF-I) axis and use of glucocorticoids (MacRae et al 2006a, Wong et al 2006. Levels of proinflammatory cytokines, such as tumour necrosis factor (TNF)-a and interleukin (IL)-1b are often raised in these diseases, and measures that block TNF-a action, such as anti-TNF therapy, lead to an improvement in growth.…”
Section: Introductionmentioning
confidence: 99%
“…It is only when the lack of the efficacy of such treatment is observed that further diagnostics are conducted, which indicate inflammatory disease of the intestines as the origin of short stature. Overproduction of pro-inflammatory cytokines, including TNF-α, INF-γ, IL-6, IL-12, IL-17, IL-23, and IL-1β, plays a key role in the M Ma ac cr ro o--a an nd d m mi ic cr ro o--n nu ut tr ri ie en nt t d de ef fi ic ci ie en nc ci ie es s N Nu ut tr ri ie en nt ts s P Pe er rc ce en nt ta ag ge e o of f C CD D p pa at ti ie en nt ts s w wi it th h d de ef fi ic ci ie en nc ci ie es s [14] resistance mechanism of tissue resistance to the action of hormonal factor stimulating the growth process [16][17][18]. Studies on animals have documented a pivotal role of IL-6, which induces growth inhibition due to the suppression of IGF-1 secretion.…”
Section: Hormonal and Inflammatory Factorsmentioning
confidence: 99%
“…Inadequate secretion or deficiency of growth hormone (GH) and insulin-like growth factor 1 (IGF-1), GH/IGF-1 axis disturbances as well as tissue resistance to the action of those factors are the main features of hormonal disturbances in children with inflammatory bowel disease [15,16]. Bioavailability of IGF-1 (somatomedin C) depends on its free fraction and on its serum carriers, namely binding proteins (IGFBPs: IGFBP-1 to IGFBP-6).…”
Section: Hormonal and Inflammatory Factorsmentioning
confidence: 99%
“…Linear growth can be also expressed as height velocity which represents growth status at a particular point of time and might present a more sensitive marker for the impact of disease on normal growth, particularly in peripubertal children. Severe growth impairment has been defined as height velocity SDS below -1 [2].…”
Section: Definition and Prevalencementioning
confidence: 99%